2007
DOI: 10.1210/jc.2006-2527
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Desacylated and Acylated Ghrelin and Insulin Sensitivity in the Metabolic Syndrome

Abstract: Obesity could alter circulating ghrelin profile, and relative A-Ghr excess could contribute to obesity-associated insulin resistance in metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
172
2
25

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(216 citation statements)
references
References 25 publications
15
172
2
25
Order By: Relevance
“…[2][3][4] However, the potential differences between the different ghrelin forms under these pathophysiological conditions are controversial and remain largely undefined. [34][35][36][37][38] As expected, our data show decreased plasma desacyl ghrelin levels in obese patients, which is in accordance with studies carried out by other authors. [34][35][36][37][38] Nonetheless, we found, for the first time, that plasma acylated ghrelin levels are increased in obesity and obesity-associated T2D.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[2][3][4] However, the potential differences between the different ghrelin forms under these pathophysiological conditions are controversial and remain largely undefined. [34][35][36][37][38] As expected, our data show decreased plasma desacyl ghrelin levels in obese patients, which is in accordance with studies carried out by other authors. [34][35][36][37][38] Nonetheless, we found, for the first time, that plasma acylated ghrelin levels are increased in obesity and obesity-associated T2D.…”
Section: Discussionsupporting
confidence: 92%
“…[34][35][36][37][38] As expected, our data show decreased plasma desacyl ghrelin levels in obese patients, which is in accordance with studies carried out by other authors. [34][35][36][37][38] Nonetheless, we found, for the first time, that plasma acylated ghrelin levels are increased in obesity and obesity-associated T2D. The elevation of circulating acylated ghrelin concentrations in obese individuals may play a role in obesity-associated hyperphagia and adiposity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that ghrelin concentrations of patients with type 2 diabetes was significantly lower (P<0.05) than those of controls group which was in line with previous studies [7,[15][16][17]. Our findings support the view that low ghrelin level could have a causative role in the development of type 2 diabetes.…”
Section: Ghrelin Concentrations In the Studied Groupssupporting
confidence: 92%
“…Moreover, insulin-resistant obese subjects have an elevated AG:DAG ratio when compared with insulin-sensitive obese subjects (10,11,12). These findings suggest that the inhibition of ghrelin might be beneficial for glycemic control and body composition.…”
Section: Introductionmentioning
confidence: 85%